A benefit–cost analysis of different response scenarios to COVID‐19: A case study. Issue 2 (4th June 2021) - Cook, David C.; Fraser, Rob W.; McKirdy, Simon J.
Abstract: Background: This paper compares the direct benefits to the State of Western Australia from employing a "suppression" policy response to the COVID‐19 pandemic rather than a "herd immunity" approach. Methods: An S‐I‐R (susceptible‐infectious‐resolved) model is used to estimate the likely benefits of a suppression COVID‐19 response compared to a herd immunity alternative. Direct impacts of the virus are calculated on the basis of sick leave, hospitalizations, and fatalities, while indirect impacts related to response actions are excluded. Results: Preliminary modeling indicates that approximately 1700 vulnerable person deaths are likely to have been prevented over 1 year from adopting a suppression response rather than a herd immunity response, and approximately 4500 hospitalizations. These benefits are valued at around AUD4.7 billion. If a do nothing policy had been adopted, the number of people in need of hospitalization is likely to have overwhelmed the hospital system within 50 days of the virus being introduced. Maximum hospital capacity is unlikely to be reached in either a suppression policy or a herd immunity policy. Conclusion: Using early international estimates to represent the negative impact each type of policy response is likely to have on gross state product, results suggest the benefit–cost ratio for the suppression policy is slightly higher than that of the herd immunity policy, but both benefit–cost ratios are less than one.